Clinical Outcome of Discordant Empirical Therapy and Risk Factors Associated to Treatment Failure in Children Hospitalized for Urinary Tract Infections - Giovanni Autore; Cosimo Neglia; Margherita Di Costanzo; Martina Ceccoli; Gianluca Vergine; Claudio La Scola; Cristina Malaventura; Alice Falcioni; Alessandra Iacono; Antonella Crisafi; Lorenzo Iughetti; Maria Luisa Conte; et al. (MDPI AG, 2022)
With the spread of antibiotic resistance in pediatric urinary tract infections (UTIs), more patients are likely to be started empirically on antibiotics to which pathogens are later found to be resistant (discordant therapy). However, in-vivo effectiveness may be different from in-vitro susceptibility. Aims of this study were to describe clinical outcomes of discordant empirical treatments in pediatric UTIs and to investigate risk factors associated to treatment failure. This observational, retrospective study was conducted on children hospitalized for febrile UTIs with positive urine culture and started on discordant empirical therapy. Failure rates of discordant treatments and associated risk factors were investigated. A total of 142/1600 (8.9%) patients were treated with inadequate empirical antibiotics. Clinical failure was observed in 67/142 (47.2%) patients, with no fatal events. Higher failure rates were observed for combinations of penicillin and beta-lactamase inhibitors (57.1%). Significant risk factors for failure of discordant treatment were history of recurrent UTIs (95% CI: 1.13-9.98, OR: 3.23, p < 0.05), recent use of antibiotics (95% CI: 1.46-21.82, OR: 5.02, p < 0.01), infections caused by Pseudomonas aeruginosa (95% CI: 1.85-62.10, OR: 7.30, p < 0.05), and empirical treatment with combinations of penicillin and beta-lactamase inhibitors (95% CI: 0.94-4.03, OR: 1.94, p = 0.05). This study showed that discordant empirical treatments may still be effective in more than half of pediatric UTIs. Clinical effectiveness varies between different discordant antibiotics in pediatric UTIs, and patients presenting risk factors for treatment failure may need a differentiated empirical approach.